2013
DOI: 10.1590/s1676-24442013000400011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy between fine needle aspiration biopsy (FNA) and pathological examination of the thyroid

Abstract: Introduction: Despite the fact that the fine needle aspiration biopsy (FNA) is commonly used in the initial evaluation and distinction of benign and malignant lesions of thyroid nodules, it may yield variable results, inasmuch as it is contingent on the pathologist's analysis and expertise in collecting appropriate samples. Objective: To check the diagnostic accuracy between FNA and pathological examination of thyroid nodules, both performed in a diagnostic pathology service. Methods: Retrospective study carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…12 Similarly, Patel NR et al also found the most common lesion was colloid goiter with 36% of people were affected. 10 In this study also the most common nodules were colloid goiter 35.1%, followed by Hashimoto thyroiditis 25.5% and nodular goiter 20.2% by FNAC. USG shows colloid goiter 36.17% was the most common followed by nodular goiter 22.34% and hasimato19.14%.…”
Section: Discussionsupporting
confidence: 60%
“…12 Similarly, Patel NR et al also found the most common lesion was colloid goiter with 36% of people were affected. 10 In this study also the most common nodules were colloid goiter 35.1%, followed by Hashimoto thyroiditis 25.5% and nodular goiter 20.2% by FNAC. USG shows colloid goiter 36.17% was the most common followed by nodular goiter 22.34% and hasimato19.14%.…”
Section: Discussionsupporting
confidence: 60%
“…This is further substantiated by many authors in their studies [9,10]. However the increased concern on cosmesis and the higher health seeking behaviour in females may be additional factors favoring this.…”
Section: Discussionmentioning
confidence: 73%
“…This is further substantiated by many authours in their studies. (9,10) However the increased concern on cosmesis and the There is a wide variation in the global statistics relating to the validity of FNAC as a tool for diagnosing thyroid pathology. The…”
Section: Discussionmentioning
confidence: 99%